Accuracy of preoperative ultrasound measurement of rectus diastasis compared to in vivo findings: a comparative study - Brett K Sacks; Carmen Munteanu; Frank Lin; Dean C White (Australasian Journal of Plastic Surgery)
**Introduction**: In July 2022 a new Medicare Benefits Schedule (MBS) item number 30175 was created for a radical abdominoplasty with rectus diastasis repair. To qualify for this benefit and attain a significant reduction in their out-of-pocket surgical cost, patients are required to undergo preoperative radiological assessment of their rectus diastasis with a measured inter-rectal distance (IRD) of 3 cm or more. This study examines the relationship between preoperative radiological evaluation of the IRD and intraoperative measurements for patients undergoing abdominal wall procedures with rectus diastasis repair.